Assessment of temperature optimum signatures of corals at both latitudinal extremes of the Red Sea. Issue 1 (18th February 2022) - Banc-Prandi, Guilhem; Evensen, Nicolas R; Barshis, Daniel J; Perna, Gabriela; Moussa Omar, Youssouf; Fine, Maoz
Abstract : Thermal performance assays were conducted on six common reef-building coral species from the northern and the southern Red Sea (2000 km apart). Most species displayed similar temperature optima ( Topt ), suggesting an exceptional continuity in their physiological performances across such a large latitudinal range. Abstract: Rising ocean temperatures are pushing reef-building corals beyond their temperature optima ( Topt ), resulting in reduced physiological performances and increased risk of bleaching. Identifying refugia with thermally resistant corals and understanding their thermal adaptation strategy is therefore urgent to guide conservation actions. The Gulf of Aqaba (GoA, northern Red Sea) is considered a climate refuge, hosting corals that may originate from populations selected for thermal resistance in the warmer waters of the Gulf of Tadjoura (GoT, entrance to the Red Sea and 2000 km south of the GoA). To better understand the thermal adaptation strategy of GoA corals, we compared the temperature optima ( Topt ) of six common reef-building coral species from the GoA and the GoT by measuring oxygen production and consumption rates as well as photophysiological performance (i.e. chlorophyll fluorescence) in response to a short heat stress. Most species displayed similar Topt between the two locations, highlighting an exceptional continuity in their respective physiological performances across such a large latitudinal range, supporting the GoA refuge theory. Stylophora pistillata showed a significantly lower Topt in the GoA, which may suggest an ongoing population-level selection (i.e. adaptation) to the cooler waters of the GoA and subsequent loss of thermal resistance. Interestingly, all Topt were significantly above the local maximum monthly mean seawater temperatures in the GoA (27.1°C) and close or below in the GoT (30.9°C), indicating that GoA corals, unlike those in the GoT, may survive ocean warming in the next few decades. Finally, Acropora muricata and Porites lobata displayed higher photophysiological performance than most species, which may translate to dominance in local reef communities under future thermal scenarios. Overall, this study is the first to compare the Topt of common reef-building coral species over such a latitudinal range and provides insights into their thermal adaptation in the Red Sea.